2018
DOI: 10.1159/000490252
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling as an Adjunctive Measure to Guide the Management of Indeterminate, High-Risk Choroidal Melanocytic Lesions: A Pilot Study

Abstract: Purpose: To describe our early experience with gene expression profiling (GEP) assessment for juxtafoveal, subfoveal, and peripapillary indeterminate high-risk melanocytic lesions to assist in making early treatment decisions in patients who did not feel comfortable with either close observation or definitive treatment. Methods: A prospective cohort of patients with indeterminate lesions who underwent GEP were enrolled. Nonparametric statistical analysis was utilized given the small sample size. Results: Fifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…On this basis, it is conventional practice in many ocular oncology centers to monitor small, indeterminate uveal melanocytic tumors for months (or even years) until growth is documented [ 68 , 69 , 70 , 71 , 72 ]. Weis et al demonstrated that most of these indeterminate lesions are low-risk D3-UM [ 73 ]. Our current study supports these findings, with 73% of the small melanocytic tumors being D3; however, importantly, we demonstrate that over one quarter (i.e., 27%) of these small lesions are M3-UM, and therefore have a high metastatic risk.…”
Section: Discussionmentioning
confidence: 99%
“…On this basis, it is conventional practice in many ocular oncology centers to monitor small, indeterminate uveal melanocytic tumors for months (or even years) until growth is documented [ 68 , 69 , 70 , 71 , 72 ]. Weis et al demonstrated that most of these indeterminate lesions are low-risk D3-UM [ 73 ]. Our current study supports these findings, with 73% of the small melanocytic tumors being D3; however, importantly, we demonstrate that over one quarter (i.e., 27%) of these small lesions are M3-UM, and therefore have a high metastatic risk.…”
Section: Discussionmentioning
confidence: 99%
“…Although with recent innovations in imaging we are able to detect subtle changes such as orange pigmentation and subretinal fluid that were barely detectable on clinical examination, the diagnostic dilemma persists [2, 3]. The issue has become more relevant with the use of commercially available molecular prognostic tests (which have been validated only for survival prognosis) [4], as a surrogate for diagnosis of small choroidal melanomas [5-7]. For the purpose of this commentary, the complex clinical situation could be broken down to certain key components.…”
Section: Introductionmentioning
confidence: 99%
“…Few attempts have been made to correlate growth [23] or growth “risk factors” (clinical characteristics) across various AJCC stages [24] and more specifically in small choroidal melanoma with a prognostic class (indicator for metastasis) using 2 commercially available prognostic tests, MLPA (Impact Genetics, Toronto, Canada) [25] and GEP (DecisionDx-UM; Castle Biosciences, Inc., Phoenix, AZ, USA) [26] (Table 1) [27, 28]. The limited data indicate that the growth “risk factors” such as presence of orange pigment, subretinal fluid (SRF), and lack of drusen/ retinal pigment epithelial (RPE) changes are not statistically significantly associated with metastatic potential as identified by GEP class [24, 28].…”
Section: Introductionmentioning
confidence: 99%
“…The limited data indicate that the growth “risk factors” such as presence of orange pigment, subretinal fluid (SRF), and lack of drusen/ retinal pigment epithelial (RPE) changes are not statistically significantly associated with metastatic potential as identified by GEP class [24, 28]. Relationship with tumor height seems to be conflicting between the studies [24, 27, 28]. Even documented growth, considered as a hallmark diagnostic feature of small choroidal melanoma [29-33], was not associated with the GEP class although the definition of observed growth was not specified in the study [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation